The degree of possession and practice of class teachers studying at the Open University of Sudan for the cognitive, skills and technological teaching competencies - Al-hassan, Esam Edris Kamtor; Osman, Hassan Ja'afar Mohammed (Journal of Educational and Psychological Sciences, 2021)
This research aimed at identifying the degree of possession and practice of class teachers studying at the Open University of Sudan (O.U.S) for the cognitive, skills and technological teaching competencies. The descriptive analytical methodology is used. The research population consists of basic school teachers working in public schools in Al Gazira Educational region affiliated to O.U.S the 5th group, whose total number was (120) beside (6) educational supervisors. Two tools were used for data collection; a questionnaire and an observation forms. Data was analyzed by using the suitable statistical methods. The most important results that the research concluded were: The degree of possession of class teachers studying at the O.U.S for cognitive competencies came at a high degree, with the average of (3.69), and a high degree with the average of (3.58) for skill competencies. As for the degree of class teachers ’possession of technological competencies, it was of a medium degree, with the average of (3.47).The overall degree of the class teachers 'practice estimates at the O.U.S for teaching competencies, from the supervisors' point of view was high, with the average of (3.55).There is no statistically significant difference for class teachers at the basic education stage, who are studying at the O.U.S with regard to their possession teaching competencies due to the gender variable.
Keywords: teaching competencies; Class teachers; Sudan Open University